POLÍTICA PÚBLICA PENITENCIARIA Y CARCELARIA EN EL CONTEXTO DE LOS PROCESOS DE REINSERCIÓN SOCIAL EN COLOMBIA (2016)
The current public penitentiary and prison policy does not adapt itself to the penitentiary guidelines in the context of the process of social reintegration of convicted people in Colombia. This article carries out an analysis of the process of social reintegration, as well as a diagnosis of the problems facing the current system, the situation of laws and their impact, against the responsibility of the State due to its constant violation of these laws, in the sense that if it still exclusively rules the coercive will, or if on the contrary, the idea centres on the respect of these laws in the national penitentiary system This is combined with the impact of the current public policy to the process of social reintegration, together with a comparative study of different legislation.